Functional Imaging in the Follow-Up of Enteropancreatic Neuroendocrine Tumors: Clinical Usefulness and Indications - Merola, Elettra; Pavel, Marianne E.; Panzuto, Francesco; Capurso, Gabriele; Cicchese, Noemi; Rinke, Anja; Gress, Thomas M.; Iannicelli, Elsa; Prosperi, Daniela; Pizzichini, Patrizia; Prasad, Vikas; Kump, Patrizia; et al. (The journal of clinical endocrinology and metabolism, 2017)
Functional imaging tests (FITs) detecting somatostatin receptor expression [i.e., somatostatin receptor scintigraphy, 68Ga-DOTA positron emission tomography/computed tomography (CT)] have a pivotal role in the diagnosis of neuroendocrine tumors (NETs), although their indication during follow-up still needs to be clarified. Investigate the role of FITs after diagnosis of metastatic enteropancreatic NETs, identifying patients who might benefit from these exams. Multicenter retrospective analysis of metastatic enteropancreatic NETs. Analysis of imaging tests performed between January 1995 and December 2015 in Rome, Berlin, Milan, Marburg, or Graz. One hundred forty-three patients with metastatic pancreatic NETs and small intestine NETs, at least 2-year follow-up, and positive FITs. Patients had received CT every 6 months (unless clinical conditions and tumor behavior required shorter intervals) and FIT every 12 months. Clinical usefulness of FITs, defined as changes in patient management (indication to biopsy, medical therapy, surgery, or further imaging tests) due only to FITs. FITs affected management in 73.4% of patients, mostly when G2 vs G1 [odds ratio (OR), 2.40; 95% confidence interval (CI), 1.09 to 5.27; P = 0.03]. Changes were observed in a 12-month time frame especially with pancreatic NETs vs small intestine NETs (OR, 2.89; 95% CI, 1.09 - 7.67; P = 0.03) or metastases since diagnosis vs developed during follow-up (OR, 4.00; 95% CI, 1.43 to 11.17; P < 0.01). FITs used in addition to CT in the follow-up of stage IV enteropancreatic NETs improve patient management (especially for G2 tumors). Follow-up program should be tailored according to tumor features.